"EFFECTIVE VOLUNTEERISM:" HELPING CHILD CAREGIVERS IN DEVELOPING COUNTRIES. Issue 6 (2nd November 2016) - Murray Harrison, Alexandra
ABSTRACT: This article proposes a method of volunteering mental health consultation to child caregivers in developing countries in the context of episodic visits and a long‐term relationship. It is derived from the author's experience doing this work for approximately 12 years. The two foundational features of the method—the role of a consultant and a long‐term relationship—are described. The method is then elaborated in two settings: consultation to caregivers in an orphanage in Central America and at a hospital in India. While these examples are distinct in multiple domains, they have in common the core features of the consultative model and a long‐term relationship. Finally, the article briefly addresses challenges that the consultant experiences when working with neglected and traumatized children and the usefulness of reflective practice. It is hoped that an articulation of this method may make it possible for many who might wish to volunteer to do so, in a way that neither interferes significantly with their work and family life at home nor creates the problems of "helicopter volunteering."